Quartz and orthopyroxene exsolution lamellae in clinopyroxene and the metamorphic P–T path of Belomorian eclogites. (29th September 2017) - Li, Xiaoli; Zhang, Lifei; Wei, Chunjing; Slabunov, Alexander I.; Bader, Thomas
ABSTRACT: The Shirokaya Salma eclogite‐bearing complex is located in the Archean–Palaeoproterozoic Belomorian Province (Russia). Its eclogites and eclogitic rocks show multiple clinopyroxene breakdown textures, characterized by quartz–amphibole, orthopyroxene and plagioclase lamellae. Representative samples, a fresh eclogite, two partly retrograded eclogites, and a strongly retrograded eclogitic rock, were collected for this study. Two distinct mineral assemblages—(1) omphacite+garnet+quartz+rutile±amphibole and (2) clinopyroxene+garnet+amphibole+plagioclase+quartz+rutile+ilmenite±orthopyroxene—are described. Based on phase equilibria modelling, these assemblages correspond to the eclogite and granulite facies metamorphism that occurred at 16–18 kbar, 750–800°C and 11–15 kbar, 820–850°C, respectively. The quartz–amphibole lamellae in clinopyroxene formed during retrogression with water ingress, but do not imply UHP metamorphism. The superfine orthopyroxene lamellae developed due to breakdown of an antecedent clinopyroxene (omphacite) during retrogression that was triggered by decompression from the peak of metamorphism, while the coarser orthopyroxene grains and rods formed afterwards. The P–T path reconstructed for the Shirokaya Salma eclogites is comparable to that of the adjacent 1.9 Ga Uzkaya Salma eclogite (Belomorian Province), and those of several other Palaeoproterozoic high‐grade metamorphic terranes worldwide, facts allowing us to debate the exact timing of eclogite facies metamorphism in the Belomorian Province.